2008
DOI: 10.1186/1471-2164-9-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible nets: disorder and induced fit in the associations of p53 and 14-3-3 with their partners

Abstract: Background: Proteins are involved in many interactions with other proteins leading to networks that regulate and control a wide variety of physiological processes. Some of these proteins, called hub proteins or hubs, bind to many different protein partners. Protein intrinsic disorder, via diversity arising from structural plasticity or flexibility, provide a means for hubs to associate with many partners (Dunker AK, Cortese MS, Romero P, Iakoucheva LM, Uversky VN: Flexible Nets: The roles of intrinsic disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
533
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 527 publications
(555 citation statements)
references
References 150 publications
13
533
3
Order By: Relevance
“…Furthermore, the acetate groups both became buried in the interfaces between the two MoRFs and their respective partners. 48 In this study, we discovered that differences in PTMs occur commonly when MoRFs bind to alternative partners. Furthermore, this use of modified side chains to bind to one of two partners is most common when the two partners are structurally distinct.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, the acetate groups both became buried in the interfaces between the two MoRFs and their respective partners. 48 In this study, we discovered that differences in PTMs occur commonly when MoRFs bind to alternative partners. Furthermore, this use of modified side chains to bind to one of two partners is most common when the two partners are structurally distinct.…”
Section: Discussionmentioning
confidence: 94%
“…Using sequence characteristics that indicate short binding regions within longer regions of disorder offers a second strategy that does not depend on specific motifs, and several predictors have been developed that use this second strategy. [46][47][48][49][50] Such predictors have been used by experimentalists to help with the identification of binding regions within longer regions of disorder. 39,51 Both a hub protein's ability to bind multiple partners and the general importance of PPIs suggest that the use of flexibility for partner binding by IDPs and IDP regions is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Here, B70% of the interactions of p53 are mediated by IDPRs containing 86, 90, and 100% of observed acetylation, phosphorylation, and protein conjugation sites of this protein, respectfully. 42 Early on, X-ray and NMR structural analysis revealed that an important inhibitor of PCD, BCL-x L , contains a 60-residue IDPR connecting helices al and a2. 43 Other members of the BCL-2 family, BH3-only proteins (such as BIM, BAD, and BMF) that serve as key initiators of PCD are largely disordered in solution.…”
Section: Discussionmentioning
confidence: 99%
“…Disorder also allows some very unusual interactions; the yeast ubiquitin ligase San1, for example, recognizes misfolded substrates [159] and the CDK inhibitor Sic1 interacts with a single site on Cdc4 via multiple dispersed phosphorylation sites [158]. The hub proteins already mentioned frequently contain disordered regions [160] that are used to interact with a variety of partners [93].…”
Section: Disordered Proteins and Protein Segments Are Crucial For Celmentioning
confidence: 99%